Paramutation: the tip of an epigenetic iceberg? - Suter, Catherine M. (2009)
Paramutation describes the transfer of an acquired epigenetic state to an unlinked homologous locus, resulting in a meiotically heritable alteration in gene expression. Early investigations of paramutation characterized a mode of change and inheritance distinct from mendelian genetics, catalyzing the concept of the epigenome. Numerous examples of paramutation and paramutation-like phenomena have now emerged, with evidence that implicates small RNAs in the transfer and maintenance of epigenetic states. In animals piRNA-mediated retrotransposon suppression seems to drive a vast system of epigenetic inheritance with paramutation-like characteristics. The classic examples of paramutation might be merely informative aberrations of pervasive and broadly conserved mechanisms that use RNA to sense homology and target epigenetic modification. When viewed in this context, paramutation is only one aspect of a common and broadly distributed form of inheritance based on epigenetic states.